Branding Strategies for Islamic Educational Institutions in Improving the Competitiveness of Madrasahs - Suwandi Suwandi (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2025)
The purpose of writing this article is: (1) to find out how the branding strategy is implemented at MIN 1 Jombang, and (2) to find out what the branding strategy is at MI Mujahidin Parimono Jombang. This research method uses a qualitative approach with a case study type of research. Data collection was carried out using interviews, observation, and documentation. Data analysis techniques using data reduction stages, data presentation, and concluding/data verification. The validity of the data was established using triangulation techniques. The results of research on the branding strategy of Islamic educational institutions in increasing competitiveness are as follows: 1) The branding strategy at MIN 1 Jombang is carried out in several ways as follows: (a) Madrasah Accreditation Score, (b) Madrasah superior programs (Digital Madrasah, Religion, Literacy, Child Friendly, and Adiwiyata), (c) Madrasah achievements in academic and non-academic, and (d) Extra Curricular Robotics; 2) The branding strategy at MI Mujahidin Parimono Jombang is carried out in the following way: (a) Madrasah Accreditation Score, (b) At Tartil method superior program, (c) Madrasah achievements in academic and non-academic fields